The Creativity of Class V Students in Integrated Learning in Elementary Schools: Kreativitas Siswa Kelas V Dalam Pembelajaran Terpadu Di Sekolah Dasar - Lastanti Utami; Machful Indra Kurniawan (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to describe the creativity of students in integrated learning at SDN Kemiri Sidoarjo in terms of creative thinking skills and one's attitudes and feelings. The subjects of this study were teachers and students in class V-A. This research was conducted from November to December 2019. This type of research is descriptive qualitative. Data collection data obtained by means of observation, interviews and documentation. So that the research results are as follows: 1) Student creativity in integrated learning or thematic learning at SDN Kemiri Sidoarjo can be viewed from two kinds, namely the ability to think creatively and one's attitudes and feelings. 2) Based on the results of the study, the creativity of class V-A students in thematic learning at SDN Kemiri Sidoarjo in terms of creative thinking skills is that students have fluent thinking skills, flexible or flexible thinking, detailing or elaborating and have skills in assessing. While the creativity of class V-A students in thematic learning at SDN Kemiri Sidoarjo in terms of one's attitudes and feelings is that students have imagination, feel challenged, risk-taking attitude and respect.